Creating emotion in games the craft and art of emotioneering - Freeman, David 1941- (New Riders, 2004)
An introduction to emotioneering explains how to create an emotional immersion and involvement in computer games, presenting 150 hands-on techniques--that include dialog and plot deepening, game repeatability, game and player transitioning, relationship building, and more--and features a section of case studies from well-known games.